Practice patterns and recommendations for pediatric image‐guided radiotherapy: A Children's Oncology Group report. Issue 10 (9th August 2020) - Hua, Chia‐ho; Vern‐Gross, Tamara Z.; Hess, Clayton B.; Olch, Arthur J.; Alaei, Parham; Sathiaseelan, Vythialingam; Deng, Jun; Ulin, Kenneth; Laurie, Fran; Gopalakrishnan, Mahesh; Esiashvili, Natia; Wolden, Suzanne L.; et al.
Abstract: This report by the Radiation Oncology Discipline of Children's Oncology Group (COG) describes the practice patterns of pediatric image‐guided radiotherapy (IGRT) based on a member survey and provides practice recommendations accordingly. The survey comprised of 11 vignettes asking clinicians about their recommended treatment modalities, IGRT preferences, and frequency of in‐room verification. Technical questions asked physicists about imaging protocols, dose reduction, setup correction, and adaptive therapy. In this report, the COG Radiation Oncology Discipline provides an IGRT modality/frequency decision tree and the expert guidelines for the practice of ionizing image guidance in pediatric radiotherapy patients.